Replication of “Procrastination, Deadlines, and Performance: Self-Control by Precommitment” - Hyndman, Kyle; Bisin, Alberto (Psychological Science, 2026)
We present the results of a replication of Study 2 from Ariely and Wertenbroch on the role of deadlines in mitigating procrastination. We show that our results do not replicate those of the original article. In our replication, with adult participants enrolled at a large public university in the United States, changes in the deadlines had a negligible effect on the three performance metrics and several survey metrics used in the original study. Evenly spaced deadlines, externally imposed on participants by the experimenters, did not stand out for their effectiveness in reducing procrastination in participants. The data further indicate consistency with several patterns of participant behavior that should be expected irrespective of our main replication results.